Evaluation of supraharmonic emission levels of multiple grid‐connected VSCs. Issue 24 (21st November 2019) - Wang, Ying; Luo, Daijun; Xiao, Xianyong
Abstract : Supraharmonic is an inevitable power quality issue, with the rapid development of power electronic technologies, receiving more and more attention. Firstly, this study analyses the supraharmonic emission mechanism of voltage source converter (VSC) based on sinusoidal pulse‐width modulation. The mathematical analysis shows that the supraharmonics emitted by grid‐connected VSC mainly distribute near the integer multiple of its switching frequency, and grid‐connected VSCs are essentially supraharmonic voltage sources. Then, this study proposes the supraharmonic equivalent circuit model of multiple VSCs grid‐connected system, by modelling grid‐connected VSCs as supraharmonic voltage sources and connecting them in parallel with the LCL filters. Based on the proposed model, considering the primary and secondary emissions, a method is proposed to evaluate the supraharmonic current emission of one VSC and the total supraharmonic current emission flowing into the grid. Finally, simulation and field measurements show that the proposed method can effectively evaluate the supraharmonic emission levels of multiple VSCs grid‐connected systems.